Pengaruh Latihan Single Leg Bound dan Split Jump Terhadap Kemampuan Servis Punggung Sepak Takraw - Aditya Ilham (YLPK Mahardhika, 2021)
The Effect of Single Leg Bound and Split Jump Exercises on the Back Service Ability of the Sepak Takraw Klub Academy Sepak Takraw Foundation (ASTF) Dukuhseti